Examining the Impact of Project-Based Learning on Students’ Academic Writing Development in Indonesian Language Education - Taufik Taufik; Diana Purwati; Muhammad Riskan (Journal of Insan Mulia Education, 2026)
The development of students’ academic writing skills remains a persistent challenge in language education, particularly in fostering meaningful learning engagement and process-oriented writing practices. This study analyzes the impact of Project-Based Learning on students’ academic writing skills in Indonesian language education. The study employed an explanatory sequential mixed methods design involving 29 eighth-grade students. Quantitative data were obtained through pre-test and post-test writing assessments and analyzed using a paired sample t-test, while qualitative data were collected through classroom observations and semi-structured interviews and analyzed thematically. The quantitative results indicated a significant improvement in students’ writing performance after the implementation of PjBL. The qualitative findings showed that this improvement was associated with increased student engagement, a more structured writing process, and collaborative learning experiences that supported idea development and writing quality. These findings suggest that improvements in writing skills are influenced not only by instructional design but also by participation and interaction during the learning process. This study contributes to an integrated understanding of how PjBL supports academic writing development through a mixed methods approach. The findings emphasize the importance of process-oriented, collaborative, and authentic writing instruction. Overall, the study confirms the potential of PjBL to foster meaningful and sustainable development of students’ writing skills.